(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
Composite materials are one of the most promising directions in modern industry due to their advantages such as light weight, high strength, corrosion resistance, long service life, and structural flexibility. In particular, the share of composites is steadily increasing in aviation, automotive engineering, construction, energy, medicine, and the sports industry.